1992
DOI: 10.1071/ar9920451
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light and temperature on in vitro germination and germ tube growth of urediniospores of Tranzschelia discolor

Abstract: The effect of light on in vitro germination of urediniospores of Tranzschelia discolor was studied over time at different intensitities (up to 400 8E m-2 s-l) within the temperature range 5�C to 20�C. A model was also developed from the data to predict germination at different combinations of light, temperature and times of leaf wetness. Light retarded the germination process, and its effect increased in direct proportion to intensity. At 20�C, for example, the time taken to exceed 80% germination increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…vaccinni, P. hemerocallidis and Ph. pachyrhizi and to a lesser extent P. menthae in the present study is consistent with work on several rust fungi (Ellison et al 1992;Givan and Bromfield 1964a, b;Hocking 1968;Joseph and Hering 1997;Knight and Lucas 1980;Singh and Heather 1982;Sood and Sackston 1972). While urediniospore germination can indicate the relative sensitivity of rust fungi to light it was interesting to observe that germ tube elongation of all species in the current study were negatively affected by light.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…vaccinni, P. hemerocallidis and Ph. pachyrhizi and to a lesser extent P. menthae in the present study is consistent with work on several rust fungi (Ellison et al 1992;Givan and Bromfield 1964a, b;Hocking 1968;Joseph and Hering 1997;Knight and Lucas 1980;Singh and Heather 1982;Sood and Sackston 1972). While urediniospore germination can indicate the relative sensitivity of rust fungi to light it was interesting to observe that germ tube elongation of all species in the current study were negatively affected by light.…”
Section: Discussionsupporting
confidence: 93%
“…This difference might be caused by several factors, including light intensity, light spectra and an interaction between light exposure and temperature. Light-induced reduction of urediniospore germination with some rust fungi is temperature sensitive (Ellison et al 1992, Joseph and Hering 1997, Singh and Heather 1982, Tollenaar and Houston 1966. In the present study temperature in the Petri dish in sunlight trials (25-35 C) was higher than in fluorescent light trials (22-24 C), although no differences were observed between treatment and dark-control dishes within experiments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After the Petri dishes were removed from the dew chamber, urediniospores were immediately killed and stained using lactophenol cotton blue (Ellison et al, 1992). Sixteen 1 cm 2 agar discs cut from the agar plate were scored for spore germination.…”
Section: Inoculation and Incubationmentioning
confidence: 99%
“…Em relação ao comprimento do tubo germinativo, Saccas & Charpentier (1971) encontraram o maior comprimento a 24ºC, na presença de um filme de água, enquanto Montoya & Chaves (1974) Também para outras ferrugens foram realizados estudos sobre as influências da temperatura na germinação e no crescimento do tubo germinativo, como a ferrugem da lentilha (Uromyces viciae-fabae (Pers.)) (ELLISON et al, 1990(ELLISON et al, , 1992NEGUSSIE et al, 2005). Segundo Negussie et al (2005), os urediniósporos da ferrugem da lentilha germinaram em mais de 80% a 10ºC , 15ºC, 20ºC e 25ºC e o comprimento do tubo germinativo foi de 66mm e 196mm, a 10ºC e 20ºC, respectivamente.…”
unclassified